3-D predrill overpressure prediction using prestack depth-migrated seismic velocity in a field of southwestern Malay Basin - Satti, I.A. (Springer Verlag, 2015)
Quantitative predrill pore pressure prediction is very important for reducing the drilling hazards. In many Tertiary basins, generation of overpressure is mainly by compaction disequilibrium due to high deposition rate and low permeability in shale. In the Malay Basin, high geothermal gradient (i.e., 40â60Â Â°C/km) and high heat flow also play an important role in generating overpressure at shallow depth. This study describes the utilization of 3-D prestack depth-migrated seismic interval velocity for predrill pore pressure prediction in a field of southwestern Malay Basin. The quality of 3-D prestack depth-migrated seismic interval velocity was enhanced by calibration with check-shot data. Modified Gardnerâs equation was used to generate the 3-D density cube from the interval velocity. The Eaton and Bowers methods were used to compute and predict pore pressure values from the seismic velocity. The Eaton method with standard exponent for seismic velocity gave good prediction in the shallower zone where overpressure is caused by undercompaction mechanism, whereas underpredicted the high pore pressure at the greater depth where fluid expansion is the cause of overpressure. However, the overpressures were predicted quite well by applying correction on the Eaton method for fluid expansion mechanism. Â© 2014, Saudi Society for Geosciences.